Implementasi Strategi E-Marketing pada Pietro’s Gelato - So, Idris Gautama; Fransiska, Hellen; Tjoe, Tjia Fie (Bina Nusantara University, 2008)
Pietro’s Gelato is a firm producing food and beverages, in particular ice cream. This paper aims to study the marketing strategy utilized by Pietro’s Gelato and analyses its business process, information needs and problems faced by Pietro’s Gelato’s marketing department. Analysis is conducted using Porter’s analysis method, SWOT and e-marketing seven steps analysis. Literature study is conducted by collecting materials from books and internet access which will be used to fulfill additional data needs. Survey is also conducted towards Pietro’s Gelato to obtain complete data. Implementation of e-marketing strategy in the firm to enlarge marketing coverage and also to solve marketing problems in Pietro’s Gelato. It can be concluded that from the analysis conducted and also the implementation, e-marketing strategy profits the company in terms of easier product marketing and understanding market needs.